Propagation of mussaenda by stem cuttings - Protacio, Calixto M. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 1999)
Different Mussaenda varieties were screened to ascertain their rooting ability. For 'Doña Luz', 'Queen Sirikit', 'Paraluman', 'Doña Hilaria' and 'Doña Aurora', auxin application was not necessary while for 'Mutya', 'Gining Imelda', 'Doña Paciencia', 'Lakambini', 'Diwata' and 'Doña Eva' auxin was needed to enhance and accelerate rooting. Best rooting was observed from cuttings taken from current growth which are partially mature and green. These cuttings responded well to a 15-30 min dip in 100 ppm indolebutyric acid (IBA) prior to sticking to the rooting bed. IBA combined with dopamine or IBA combined with paclobutrazol enhanced rooting of Mussaenda 'Lakambini' cuttings. In these two treatments, the extent of root development was Tegnol higher compared to IBA, paclobutrazol and dopamine applied alone.